2000
DOI: 10.1074/jbc.m001950200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interleukin-1 Receptor-associated Kinase in Normal and Endotoxin-tolerant Cells

Abstract: Interleukin-1 receptor-associated kinase (IRAK), a signal transducer for interleukin-1, has also been suggested to participate in the Toll-like receptor-mediated innate immune response to bacterial endotoxin lipopolysaccharide (LPS). Using the human promonocytic THP-1 cell line, we demonstrated that the endogenous IRAK is quickly activated in response to bacterial LPS stimulation, as measured by its in vitro kinase activity toward myelin basic protein. LPS also triggers the association of IRAK with MyD88, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(241 citation statements)
references
References 26 publications
11
224
2
4
Order By: Relevance
“…This microRNA has been identified as critical for endotoxin-induced tolerance (45,(48)(49)(50)(51)(52)(53)(54). Shao et al (59) demonstrated the association between the miR-146a gene and severe sepsis in 226 septic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This microRNA has been identified as critical for endotoxin-induced tolerance (45,(48)(49)(50)(51)(52)(53)(54). Shao et al (59) demonstrated the association between the miR-146a gene and severe sepsis in 226 septic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators suggested that ET in human monocytes and mouse macrophages is associated with decreased TLR4-MyD88-IRAK complex formation, impairment of IRAK-1 activity, and TRAF6 expression (45)(46)(47)(48)(49). In this regard, miRNAs have emerged as an important regulatory mechanism for gene expression of a number of TLR4 pathway components during ET (49); in particular, miR146a is critical for ET development in human monocytes (48,(50)(51)(52)(53)(54). As shown in Fig.…”
Section: Potential Intracellular Signaling Implicated In Et: the Rolementioning
confidence: 98%
“…Interestingly, the effects in these cell types are in agreement to that what we observed for intestinal mIC cl2 epithelial cells. Tolerance and cross-tolerance between TLR2 and TLR4 upon long-term (24 h) TLR activation has been attributed to changes in expression of TLRs, as well as to the function of several signaling molecules including IRAK-1, NF-B and MAP kinases (Dobrovolskaia et al, 2003;Li et al, 2000Li et al, , 2006Medvedev et al, 2000Medvedev et al, , 2002Otte et al, 2004;Wang et al, 2002). Whether differences in signalling molecules also contribute to the here observed TLR (cross)-regulation upon short-term TLR activation in mIC cl2 cells awaits detailed investigation of the cell signalling dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined expression of downstream regulators of the LPS/TLR4 signaling pathway. As IRAK-1 and IRAK-4 are essential components of signaling through the Toll/IL-1 receptor complex and have been shown to be downregulated in monocyte/macrophage cell lines rendered endotoxin tolerant (24,25), we first examined IRAK-1 and IRAK-4 expression in pulmonary macrophages isolated from septic and control animals. In these experiments, the total population of pulmonary macrophages (alveolar plus interstitial) was isolated from lung digests by adherence purification in order to obtain sufficient number of cells for mRNA and protein analysis.…”
Section: Figurementioning
confidence: 99%